2016
DOI: 10.3847/0004-637x/826/2/193
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Abundance Ratio and X-Factor of Co Isotopologues in L 1551 Shielded From Fuv Photodissociation

Abstract: We investigate the intrinsic abundance ratio of 13 CO to C 18 O and the X-factor in L 1551 using the Nobeyama Radio Observatory (NRO) 45 m telescope. L 1551 is chosen because it is relatively isolated in the Taurus molecular cloud shielded from FUV photons, providing an ideal environment for studying the target properties. Our observations cover~¢´¢ 40 40 with a resolution of~ 30 , which make up maps with the highest spatial dynamical range to date. We derive the X Xvalue on the sub-parsec scales in the range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…The same was found by Shimajiri et al (2014) in most of the studied regions towards Orion-A, which are affected by OB stars. Kong et al (2015) observed a gradient in X 13/18 with the decreasing of the A V in the southeast of the California molecular cloud, while the same was observed in L 1551, an isolated nearby star forming region that does not contain OB stars and thus it is influenced only by the far-UV from the interstellar radiation (Lin et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…The same was found by Shimajiri et al (2014) in most of the studied regions towards Orion-A, which are affected by OB stars. Kong et al (2015) observed a gradient in X 13/18 with the decreasing of the A V in the southeast of the California molecular cloud, while the same was observed in L 1551, an isolated nearby star forming region that does not contain OB stars and thus it is influenced only by the far-UV from the interstellar radiation (Lin et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…For example, Pineda et al (2010) derived the X-factor of (1.6 ∼ 12) × 10 20 cm −2 K −1 km −1 s in the Taurus molecular cloud. For L1551, Lin et al (2016) measured the X CO = 1.08 × 10 20 cm −2 K −1 km −1 s.…”
Section: Comparison Of Molecular Gas and Visual Extinctionmentioning
confidence: 99%
“…Thus, the spatial variation of the 13 CO/C 18 O abundance ratio, X13 CO /X C 18 O , is expected to reveal the area where the FUV radiation affects the cloud structure and properties. The effect of selective photodissociation is observed in several star-forming regions (Bally & Langer 1982;Lada et al 1994;Kong et al 2015;Lin et al 2016;Paron et al 2018). Shimajiri et al (2014) revealed the distribution of X13 CO /X C 18 O toward the northern part of the Orion A GMC.…”
Section: Introductionmentioning
confidence: 99%